Traumatic Spinal Injuries Cause Disproportionate Morbidity in Sports-Related Pediatric Trauma. (1st September 2019) - Hauser, Blake M; Gupta, Saksham; Cote, David J; Zaki, Mark M; Xu, Edward; Khawaja, Ayaz M; Lu, Yi; Groff, Michael W; Smith, Timothy R; Zaidi, Hasan A
Abstract: INTRODUCTION: American football injuries have placed a spotlight on the effects of contact sports on traumatic injury to the central nervous system. We sought to study the epidemiology and outcomes for traumatic sports-related spinal injuries. METHODS: We conducted a retrospective cohort analysis of pediatric patients who experienced a sports-related TSI, including spinal fractures and spinal cord injuries (SCIs), encoded within the National Trauma Data Bank from 2011 to 2014. RESULTS: We included 1723 cases of pediatric sports-related TSI, which represented 3.7% of all sports-related pediatric trauma (81% male, median age [IQR] 15 yr[13-17]). Traumatic spinal injuries arose most often from cycling accidents (47%) and contact sports (28%). The most frequently fractured regions were the thoracic (30%) and cervical spine (27%). Of patients with SCI, the cervical spine was involved in 60% of cases. The average length of stay for TSIs was 2 d (IQR 1-5) and 32% of these patients required ICU-level care. Relative to other sports-related trauma, TSIs without spinal cord involvement were associated with increased adjusted length of stay by 1.8 d (95% CI 1.6-2.0), as well as ICU-level need (adjusted odds ratio [aOR] = 1.7; 95% CI 1.4-2.0). 6.8% and 1.4% required laminectomy and fusion, respectively. Discharge to rehabilitative care or home with rehabilitative services was associated with elevated odds ratios for TSIs without SCI (aOR = 1.7; 95% CI 1.5-2.0) and TSIs with SCI (aOR = 4.0; 95% CI 3.2-5.0). Predictors of requiring rehabilitation at discharge were having a laminectomy or fusion, lower extremity injury, head injury, and thoracic injury. Although TSIs represented 4% of this cohort, they were present in 8% of patients discharged with rehabilitation and 17% of in-hospital deaths. CONCLUSION: Traumatic sports-related spinal injuries present significant morbidity in the pediatric population, especially with spinal cord involvement. The majority of cases arose from cycling and contact sports accidents, underscoring the need for improving education and safety in these activities.